Analisis Faktor yang Berhubungan dengan Kepuasan Kerja Tenaga Kesehatan Non PNS di Puskesmas Aceh Selatan - Muhammad Zaki Aurian; Agustina; Hanifah Hasnur (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Job satisfaction among non-civil servant (non-PNS) health workers plays a crucial role in determining the quality of primary health services at community health centers. However, various challenges such as inadequate salary, dual workload, work fatigue, interpersonal relationships, and career uncertainty may influence job satisfaction levels. This study aimed to analyze factors associated with job satisfaction among non-PNS health workers at Primary Health Centers in Aceh Selatan in 2025. This research used a quantitative approach with a cross-sectional design involving 86 respondents selected through total sampling from six health centers. Data were collected using structured questionnaires and analyzed using Chi-Square and Fisher’s Exact Test at a 95% confidence level. The results showed that most respondents reported inadequate salary, high dual workload, work fatigue, and high career uncertainty. More than half of respondents were dissatisfied with their jobs. Statistical analysis indicated that salary, dual workload, work fatigue, and career uncertainty were significantly associated with job satisfaction (p<0.05), while interpersonal relationships were not significantly related. These findings highlight the importance of improving compensation systems, workload management, fatigue prevention, and career clarity to enhance job satisfaction and health service quality.